Balancing Control and Flexibility in Public Expenditure Management Using Banking Sector Innovations for Improved Expenditure Control and Effective Service Delivery - Piatti-Funfkirchen, Moritz (The World Bank, 2019)
The control protocols that underlie public expenditure management have direct implications for a government's ability to pursue fiscal discipline and service delivery objectives. The literature recognizes the inherent challenge in balancing control with flexibility and that these two objectives are often in conflict with one another. This paper argues that applying a universal set of expenditure controls across all transactions naturally cannot meet both of these objectives. One the one hand, a regime with universal, tight ex ante commitment controls lends itself to prudent fiscal management but constrains the ability of service providers to react adequately to rapidly changing needs. On the other hand, loosening controls equally for all transactions would introduce fiscal risks. To overcome this conundrum, the paper argues for a paradigm shift: a purposeful policy shift that subjects high-value transactions to the full set of rigorous controls, while relaxing controls for low-value transactions that apply to important aspects of the service delivery sectors. Such controls could be built into the financial management information systems that facilitate transactions and institute these controls. However, the evidence suggests that these systems are frequently not deployed to their full potential. Flexibility is inadvertently inhibited where it is necessary without providing the controls for transactions that constitute a fiscal risk. Recognizing this problem, the paper develops a two-pronged, risk-based deployment strategy for financial management information systems: (1) deploy such systems to high-value transactions, and (2) use banking sector innovations for advance payments, such as smart cards or mobile money, to facilitate flexibility for low-value transactions without compromising the integrity of transactions or accountability